2012
DOI: 10.4049/jimmunol.1202017
|View full text |Cite
|
Sign up to set email alerts
|

FcγRIIb on Liver Sinusoidal Endothelium Clears Small Immune Complexes

Abstract: It has long been known that the ITIM-bearing IgG Fc receptor (FcγRIIb, RIIb) is expressed on liver sinusoidal endothelial cells (LSEC) and that the liver is the major site of small immune complex (SIC) clearance. Thus, we proposed that RIIb of LSEC eliminates blood-borne small immune complexes (SIC), thereby controlling IC-mediated autoimmune disease. Testing this hypothesis we found most RIIb of the mouse, fully three-quarters, to be expressed in liver. Moreover, most (90%) liver RIIb was expressed in LSEC, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
185
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(196 citation statements)
references
References 41 publications
11
185
0
Order By: Relevance
“…Whereas Ag clearance was largely maintained in FcR g-chain knockout mice and FcgRIII knockout mice, it was clearly diminished in FcgRII knockout mice, demonstrating that FcgRII, which is an inhibitory FcgR, is the main contributor to intracellular uptake of monomeric immune complexes in vivo. Although it has long been said that FcgRII could take multivalent immune complexes up into the cell in a noninflammatory way (13), to our knowledge this is the first report revealing that inhibitory FcgRIIb can efficiently internalize monomeric immune complexes without cross-linking the receptor in vivo. Furthermore, studies using PH-mIgG1-Fy in FcgRIII knockout mice and PH-v12 in hFcgRIIb Tg mice (Abs with enhanced binding to FcgRII/III in mice or FcgRIIb in humans, respectively) showed that Ag clearance was accelerated without shortening Ab half-life (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Whereas Ag clearance was largely maintained in FcR g-chain knockout mice and FcgRIII knockout mice, it was clearly diminished in FcgRII knockout mice, demonstrating that FcgRII, which is an inhibitory FcgR, is the main contributor to intracellular uptake of monomeric immune complexes in vivo. Although it has long been said that FcgRII could take multivalent immune complexes up into the cell in a noninflammatory way (13), to our knowledge this is the first report revealing that inhibitory FcgRIIb can efficiently internalize monomeric immune complexes without cross-linking the receptor in vivo. Furthermore, studies using PH-mIgG1-Fy in FcgRIII knockout mice and PH-v12 in hFcgRIIb Tg mice (Abs with enhanced binding to FcgRII/III in mice or FcgRIIb in humans, respectively) showed that Ag clearance was accelerated without shortening Ab half-life (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…However, the in vivo behavior of multivalent immune complexes still remains to be elucidated. It has been said that multivalent immune complexes were eliminated by FcgR in vivo and the fact that multivalent immune complexes are constitutively eliminated through FcgRII expressed on liver sinusoidal endothelial cells in mice (11)(12)(13)(14)(15) indicates that multivalent immune complexes bound to mFcgRII would be internalized and transferred to lysosome in vivo. Alternatively, it was also shown by an in vitro study that hFcgRIIb has a recycling capability and that an immune complex internalized by hFcgRIIb is constitutively recycled to the cell surface after internalization (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 10 to 30 minutes, the rounded morphology of B cells was lost and RFP fluorescence appeared more diffuse, possibly reflecting B cell death and/or degradation. The liver contains Kupffer cells (KCs), a population of highly phagocytic tissular macrophages, lining the sinusoids and expressing FcRs (11). When mice were injected with clodronate liposomes, a treatment that efficiently removed KCs (Figure 2A), anti-CD20 treatment was no longer effective (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…2B versus Fig. 3) is consistent with a mechanism for rapid hepatic elimination of ICs (Løvdal et al, 2000;Ganesan et al, 2012).…”
Section: Resultsmentioning
confidence: 49%